For sure, I'm gonna be going quite slowly
So if $f\in \text{Hom}(C,C')_n$
Then we want to show that $D_n(f) \in \text{Hom}(C,C')_{n-1}$
So we know $f:C_* \to C_{*+n}'$
Then $fd:C_* \to C_{*+n-1}$
As does $d'f$, so that makes sense
Now, we want to say that $D^2 = 0$
$D_{n-1}(D_n(f)) = d'(d'f - (-1)^nfd) - (-1)^{n-1}(d'f - (-1)^nfd)d$
So this gives $(-1)^{n+1}d'fd + (-1)^nd'fd = 0$
0-cycles are those $f$ such that $d'f - fd = 0$, precisely the chain maps. 0-boundaries are those $f$ such that $f = d'h - hd$, which is a homotopy from $f$ to $0$